Studi Literatur: Peranan Pembahasan dalam Membuat Karya Ilmiah - Anggraini, Liza; Muspawi, Mohamad (STKIP Pesisir Selatan, 2024)
Discussion of research results is an important part of scientific work which functions to interpret research findings, answer the problem being researched, and provide recommendations for further research. The discussion not only functions as a summary of research results, but also as an evaluation of the methodology used, as well as a critical analysis of the strengths and weaknesses of the research results. The research method used is literature study. Literature review is a research method carried out by collecting data and theoretical studies from various sources, namely books, scientific journals and scientific articles related to the study being discussed. The research method in the form of a literature review is carried out by searching for related journals and books, reading the contents of the study, studying and analyzing the literature that has been saved. The discussion must integrate research findings with existing theory and previous research, as well as provide insight into the practical and theoretical implications of the findings. the. In addition, it is important to avoid common mistakes in preparing discussions, such as repeating research results, providing excessive recommendations, or ignoring in-depth analysis of the data. A good discussion is logically structured, connects research results with relevant theory and literature, and contributes to the development of science and practice in related fields.